Preferensi Investor terhadap Instrumen Pendapatan Tetap Syariah di Tengah Ketidakpastian Ekonomi - Heru Setyowiyono; M. Nashrullah; Gayuh Kawedar; Muhamad Aqim Adlan; Dede Nurohman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Macroeconomic uncertainty that triggers volatility in equity markets has encouraged investors to rebalance their portfolios toward Sharia-compliant hedging instruments. This shift is evidenced by data from the Financial Services Authority (OJK), which recorded significant growth in the outstanding value of Sukuk instruments between 2020 and 2024. This study employs a descriptive qualitative approach based on documentary analysis of secondary data to examine the transformation of investor preferences toward Islamic fixed-income instruments in the Indonesian capital market. The findings reveal that investment allocation decisions are no longer driven solely by return maximization but are increasingly influenced by risk mitigation awareness and adherence to an Islamic worldview. Furthermore, the structural characteristics of Sukuk, which require underlying tangible assets, have proven effective in minimizing speculative practices while simultaneously supporting the growing trend of Environmental, Social, and Governance (ESG)-oriented sustainable investment. Therefore, adaptive policy formulation and continuous innovation in Islamic financial products are essential for regulators to maintain domestic market liquidity and enhance resilience against future economic contractions.